Assisted reproductive technology in neotropical deer: A model approach to preserving genetic diversity - Rola, Luciana Diniz; Buzanskas, Marcos Eli; Melo, Luciana Magalhães; Chaves, Maiana Silva; Freitas, Vicente José Figueirêdo; Duarte, José Maurício Barbanti [UNESP] (MDPI, 2021)
One of the most significant challenges in deer is the ability to maintain genetic diversity, avoiding inbreeding and sustaining population health and reproduction. Although our general knowledge of reproductive physiology is improving, it appears that the application of assisted reproductive technology (ART) will more efficiently advance wildlife conservation efforts and preserve genetic diversity. The purpose of this review is to present the most important results obtained with the use of ART in Neotropical deer. Thus, the state-of-the-art for estrus synchronization, semen technology, artificial insemination, and in vivo embryo production will be presented. In vitro embryo production (IVP) is also a biotechnology that is taking initial steps in deer. In this aspect, the approach with the proteomics of ovarian follicular fluid is being used as a tool for a better understanding of oocyte maturation. Finally, cell banks and the use of interspecific somatic cell nuclear transfer (iSCNT) as well as the use of stem cells for gametes differentiation are promising techniques.
Keywords: Artificial insemination; Cervidae; Cloning; Conservation; Embryo transfer; Germplasm banks